Similar Characteristics of Internal Software Quality Attributes for Object-Oriented Open-Source Software Projects - Santos, Mariana; Amador, Rodrigo; Bermejo, Paulo Henrique de Souza; Costa, Heitor (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2014)
Organizations are becoming increasingly concerned about software quality. In object-oriented (OO) systems, quality is characterized by measurements of internal quality attributes. An efficient and proper method to analyze software quality in the absence of fault-prone or defective data labels is cluster analysis. The aim of this paper is to find similarities among project structures by measuring characteristics of internal software quality. In a sample of 150 open-source software systems, we evaluated software using macro and micro categories. Results obtained using cluster analysis indicated that some domains such as Graphics, Games, and Development tend to have similarities in specialization, abstraction, stability, and complexity. These results exploit the ability of OO software metrics to find similar behavior across domains. The results provide an immediate view of the trends and characteristics of internal software quality of Java systems that need to be addressed so that software systems can continue to be maintainable.